Factorial analysis on the preparation of barium titanate-epoxy resin composite for antenna substrate - Nur Sofia Idayu, Didik Aprianto; Nurulfadzilah, Hasan; Nurul Izzah Izzaty, Mohd Nadzri; Nur Farhana, Mustafa; Loh, Fui Qi; Ahmad Afif, Mohd Faudzi; Nurhafizah, Abu Talip Yusof; Mohamad Shaiful, Abdul Karim (Electromagnetics Academy, 2024)
This study investigates the preparation and characterization of barium titanate-epoxy resin composites, focusing on main factors influencing the dielectric properties of that composite materials. Using a 2k fractional factorial design, the effects of heating temperature, stirring speed, stirring time, and hardening process on the permittivity were thoroughly investigated. Sixteen samples were prepared and analyzed using Design-Expert software, with permittivity measurements conducted via the waveguide method and a Vector Network Analyzer (VNA) in the 4-6 GHz range. Results show significant impacts from stirring time and speed, with optimal conditions identified as 50°C heating, 500 rpm stirring speed, three minutes stirring time, and room temperature hardening from two-level factorial analysis (TLFA). These findings provide valuable insights into the best fabrication conditions for barium titanite-epoxy resin composites, contributing to the development of antenna substrate with a permittivity value of 7.0208 and a loss tangent of 0.0238 that is suitable for high-frequency communication applications.